The principle of separation of powers in the creation of the Ukrainian state - Забарський, Владислав Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article the principle of separation of powers is investigated through the prism of its origin, formation and explanation by the famous thinkers and implementation in Ukraine. Attention is paid to the ambiguity of scientific approaches to understand this principle and the problems which are connected with its implementation on the territory of our country.